Session 4: Trying to augment response with chemotherapy: a triumph of hope over experience?. (May 2018) - Battersby, N. J.; Perez, R. O.; Baxter, N.; Moran, B.; Brown, G.
Abstract: As part of an approach to improve tumour regression and increase the proportion of patients with complete clinical and radiological response, Dr Perez reviews the methods and evidence base for augmenting therapy and thus augmenting response rates preoperatively. Much of the data reviewed were in the context of patients undergoing a watch‐and‐wait approach for rectal cancer after initial treatment with chemoradiotherapy.